An Android Augmented Reality Application for Retail Fashion Shopping - Abou El-Seoud, Samir; Taj-Eddin, Islam (International Journal of Interactive Mobile Technologies (iJIM), 2019)
this report will exhibit an outline of the basic features of Mobile Augmented Reality (MAR) and the key concepts of this technology in the Fashion Retail Industry. Several obstacles such as the necessity of putting on the garments to experience its actual view have been tackled by customers throughout the process of clothes shopping. The goal is to constringe these obstacles by creating an Augmented Reality based application that will directly solve these problems. The methodology was conducted by questioning shoppers about the different holdbacks faced during shopping. Solutions for the issues are expected to be achieved by developing an easily utilizable MAR application for targeted customers. The design of this paper involved the utilization of handed questionnaire and semi structured interviews with several store managers to gather sufficient about their sales strategy and proposing the solution of Augmented Reality utilization within the market. Augmented Reality Technology have a great potential to be utilized efficiently inside the fashion market as it will meritoriously improve the shopping experience of consumers across multiple fashion related industry channels.